Portuguese Children's Sleep Habits Questionnaire - validation and cross-cultural comparison - Filipe Glória Silva; Cláudia Rocha Silva; Lígia Barbosa Braga; Ana Serrão Neto (Jornal de Pediatria (Versão em Português), 2014)
Objective: To validate the Portuguese version of the Children's Sleep Habits Questionnaire (CSHQ-PT) and compare it to the versions from other countries. Methods: The questionnaire was previously adapted to the Portuguese language according to international guidelines. 500 questionnaires were delivered to the parents of a Portuguese community sample of children aged 2 to 10 years old. 370 (74%) valid questionnaires were obtained, 55 children met exclusion criteria and 315 entered in the validation study. Results: The CSHQ-PT internal consistency (Cronbach's α) was 0.78 for the total scale and ranged from 0.44 to 0.74 for subscales. The test-retest reliability for subscales (Pearson's cor-relations, n=58) ranged from 0.59 to 0.85. Our data did not adjust to the original 8 domains structure in Confirmatory Factor Analysis but the Exploratory Factor Analysis extracted 5 factors that have correspondence to CSHQ subscales. Conclusion: The CSHQ-PT evidenced psychometric properties that are comparable to the versions from other countries and adequate for the screening of sleep disturbances in children from 2 to 10 years old.